2004
DOI: 10.1073/pnas.0402302101
|View full text |Cite
|
Sign up to set email alerts
|

Flint mining in prehistory recorded by in situ -produced cosmogenic 10 Be

Abstract: The development of mining to acquire the best raw materials for producing stone tools represents a breakthrough in human technological and intellectual development. We present a new approach to studying the history of flint mining, using in situproduced cosmogenic 10 Be concentrations. We show that the raw material used to manufacture flint artifacts Ϸ300,000 years old from Qesem Cave (Israel) was most likely surface-collected or obtained from shallow quarries, whereas artifacts of the same period from Tabun C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Petro-archaeological studies of flints have difficulty in establishing a correlation between the artefact material and the potential sources of that material (Bressy, 2002;Briggs, 2001;Deflandre, 1935;Kars et al, 1990;Masson, 1981;Mauger, 1985;Sieveking et al, 1972;Valensi, 1957). Studies have been mostly on primary (in situ) and/or sub-primary sources, whereas gatherings of flints by prehistoric peoples were often probably made from secondary, redeposited materials such as glacial till and waterlaid gravels (Fernandes and Raynal, 2006;Hughes et al, 2010;Prothero, 1987, 1992;Stapert, 1976;Verri et al, 2004;Williams-Thorpe et al, 1999). Transformations of the flint cortex that can be identified from detailed petrographic studies are specific to some sedimentary environments (Fernandes, 2012;Fernandes et al, 2007).…”
Section: Overview Of the Alteration Of Flint Artefactsmentioning
confidence: 99%
“…Petro-archaeological studies of flints have difficulty in establishing a correlation between the artefact material and the potential sources of that material (Bressy, 2002;Briggs, 2001;Deflandre, 1935;Kars et al, 1990;Masson, 1981;Mauger, 1985;Sieveking et al, 1972;Valensi, 1957). Studies have been mostly on primary (in situ) and/or sub-primary sources, whereas gatherings of flints by prehistoric peoples were often probably made from secondary, redeposited materials such as glacial till and waterlaid gravels (Fernandes and Raynal, 2006;Hughes et al, 2010;Prothero, 1987, 1992;Stapert, 1976;Verri et al, 2004;Williams-Thorpe et al, 1999). Transformations of the flint cortex that can be identified from detailed petrographic studies are specific to some sedimentary environments (Fernandes, 2012;Fernandes et al, 2007).…”
Section: Overview Of the Alteration Of Flint Artefactsmentioning
confidence: 99%
“…The location of several Middle Pleistocene industrial areas and the study of cosmogenic isotopes in flints from the Tabun and Qesem caves indicated the existence of systematic, large scale, and long lasting human endeavors towards obtaining the stone they needed (e.g., Barkai et al 2002;Verri et al 2004Verri et al , 2005Barkai et al 2006).…”
Section: Human Behavior At the Sede Ilan Industrial Areamentioning
confidence: 99%
“…Evidence for stone quarrying during the Early Pleistocene is still not widespread (e.g., Petraglia et al 1999;Paddayya et al 2000Paddayya et al , 2006, while Middle Pleistocene quarry sites are already part of the archeological landscape at many places (e.g., Barkai et al 2002, 2006, Sampson 2006. A new study of the cosmogenic isotope 10 Be in flint artifacts from Middle Pleistocene caves in Israel has confirmed the use of quarried stone as early as 400 kyr (Verri et al 2004(Verri et al , 2005 and recent field work has uncovered several Middle Pleistocene extensive quarry complexes in Northern Israel (Barkai et al 2002(Barkai et al , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed a new approach for investigating procurement strategies of raw materials based on an in situ produced radioactive isotope of beryllium, 10 Be, in flint [21]. This approach takes advantage of the fact that 10 Be is produced inside rocks as a result of exposure to cosmic rays [12].…”
Section: Introductionmentioning
confidence: 99%